Major Biological Processes in European Tidal Estuaries 1995
DOI: 10.1007/978-94-009-0117-9_18
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dynamics in the Westerschelde estuary (SW Netherlands) estimated by means of the ecosystem model MOSES

Abstract: A tentative nitrogen budget for the Westerschelde (SW Netherlands) is constructed by means of a simulation model with thirteen spatial compartments. Biochemical and chemical processes in the water column are dynamically modeled; fluxes of dissolved constituents across the water-bottom interface are expressed by means of diagenetic equations.The model is calibrated on a large amount of observed variables in the estuary (1980)(1981)(1982)(1983)(1984)(1985)(1986) with relatively fine temporal and spatial detail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(96 citation statements)
references
References 31 publications
3
93
0
Order By: Relevance
“…The total organic carbon input (dissolved and particulate: 83·10 3 TC·yr -1 for an average total river discharge of 70 m 3 ·s -1 ) is consistent with previous estimates that give values around 100·10 3 TC·yr -1 for an average discharge of 90 m 3 ·s -1 [27,31]. Excess CO 2 represented 7 % of the DIC in the Zenne, 13 % in the Nete and 10 % in the Scheldt, Dender and Dijle.…”
Section: Carbon Fluxes Between the Rivers The Estuary And The Atmospsupporting
confidence: 89%
See 1 more Smart Citation
“…The total organic carbon input (dissolved and particulate: 83·10 3 TC·yr -1 for an average total river discharge of 70 m 3 ·s -1 ) is consistent with previous estimates that give values around 100·10 3 TC·yr -1 for an average discharge of 90 m 3 ·s -1 [27,31]. Excess CO 2 represented 7 % of the DIC in the Zenne, 13 % in the Nete and 10 % in the Scheldt, Dender and Dijle.…”
Section: Carbon Fluxes Between the Rivers The Estuary And The Atmospsupporting
confidence: 89%
“…For an average river flow of 90 m 3 ·s -1 , the total input of excess CO 2 from rivers into the estuary is estimated to 18·10 3 TC·yr -1 . The flows of carbon through the Scheldt estuary are now well documented, both by field and model approaches [8,12,13,23,24,27,31]. In contrast to highly turbid French estuaries (Gironde and Loire [1,2]), there is no evidence for carbonate dissolution or precipitation in the Scheldt estuary [23].…”
Section: Carbon Fluxes Between the Rivers The Estuary And The Atmospmentioning
confidence: 99%
“…It has been reported that the value of L N ranges from 0.20 to 0.76 and is strongly influenced by river watershed size (Behrendt and Opitz, 1999;Dumont et al, 2005;Seitzinger et al, 2002;Soetaert and Herman, 1995). According to an empirical formulation for denitrification loss as a function of watershed area (Dumont et al, 2005), L N was estimated to be 0.51 for the North River and 0.45 for the West River.…”
Section: Watershed Retentionmentioning
confidence: 99%
“…The Schelde has a long tradition of extensive anthropogenic pollution and is characterised as eutrophic (Soetaert & Herman, 1995;Struyf et al, 2004;Van Damme et al, 2005). Notwithstanding large efforts for industrial and municipal wastewater treatment during the last decade in Flanders and other parts of the catchment, water quality is still bad.…”
Section: Study Areamentioning
confidence: 99%
“…A small rise in the oxygen concentration can have a big influence on the nitrogen cycling. In the very polluted Schelde estuary, nitrogen removal is completely dominated by denitrification in the oxygen poor water column (Soetaert & Herman, 1995). An increase in oxygen concentration will decrease the pelagic denitrification rate.…”
Section: Ecological Impactsmentioning
confidence: 99%